2022
DOI: 10.3390/bioengineering9070326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsatile Flow Rate and Shunt Ratio in Bifurcated Distal Arteries on Hemodynamic Characteristics Involved in Two Patient-Specific Internal Carotid Artery Sidewall Aneurysms: A Numerical Study

Abstract: The pulsatile flow rate (PFR) in the cerebral artery system and shunt ratios in bifurcated arteries are two patient-specific parameters that may affect the hemodynamic characteristics in the pathobiology of cerebral aneurysms, which needs to be identified comprehensively. Accordingly, a systematic study was employed to study the effects of pulsatile flow rate (i.e., PFR−I, PFR−II, and PFR−III) and shunt ratio (i.e., 75:25 and 64:36) in bifurcated distal arteries, and transient cardiac pulsatile waveform on hem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…In the ICASA model, the blood flows in through the ICA and flows out from the bifurcated distal arteries, i.e., ICA distal and posterior communicating artery (PComA). Poly-hexcore meshing strategies were adopted to generate meshes for the ICASA model using ANSYS Fluent Meshing 2021 R2 (Ansys Inc., Canonsburg, PA, United States), and the mesh independence sensitivity was investigated and reported in the previous publication ( Yi et al, 2022a ). The final mesh has 2,741,603 elements with 25 prism layers, 3 peel layers, and size growth rate 1.05.…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the ICASA model, the blood flows in through the ICA and flows out from the bifurcated distal arteries, i.e., ICA distal and posterior communicating artery (PComA). Poly-hexcore meshing strategies were adopted to generate meshes for the ICASA model using ANSYS Fluent Meshing 2021 R2 (Ansys Inc., Canonsburg, PA, United States), and the mesh independence sensitivity was investigated and reported in the previous publication ( Yi et al, 2022a ). The final mesh has 2,741,603 elements with 25 prism layers, 3 peel layers, and size growth rate 1.05.…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Over past decades, many review publications summarized the efforts in studying hemodynamic factors on the pathophysiology of CAs, including varying risks associated with aneurysmal sac locations, high risk aneurysm morphologies, pre- and post-treatment states, and arterial blood flow conditions in vivo , in vitro , and in silico ( Sforza et al, 2009b ; Nieuwkamp et al, 2009 ; Nixon et al, 2010 ; Aoki and Nishimura, 2011 ; Jeong and Rhee, 2012 ; Fennell et al, 2016 ; Sheikh et al, 2020 ; Yu et al, 2021 ; Yi et al, 2022a ). Although transcranial Doppler velocimetry (TDV), as a non-invasive in vivo manner, can be used to assess cerebral mean blood flow velocity in the cerebral arteries ( Aaslid et al, 1982 ; Hart and Haluszkiewicz, 2000 ; Conde-Agudelo et al, 2015 ), this approach can only obtain values in limited local regions of the cerebral arteries rather than a thorough blood flow distribution in the arteries.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of grid verification is to reduce the discrete error as much as possible on the premise of saving computing resources. Therefore, the present grid verification mainly consists of two parts: 1) qualitatively analyze the influence of the total number of grids on the calculation results; 2) use the grid convergence index (GCI) to quantitatively evaluate the numerical precision of the target parameters ( Yi et al, 2022 ). A total of six meshes list in Table 2 are used to simulate the Denali filter case for grid verification.…”
Section: Verification and Validationmentioning
confidence: 99%
“…Therefore, the structural optimization of IVCF is always a matter of concern. Recently, computational fluid dynamics (CFD) has become a useful and effective tool to study the effect of the filter structure on hemodynamic characteristics while both in vivo test and in vitro experiment have considerable difficulties of patient volunteers, setup incapability and high cost ( Wang et al, 2019 ; Shar et al, 2020 ; Uchiyama et al, 2021 ; Yi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistical data from the World Health Organization, cardiovascular associated diseases have become the topmost cause of death [ 1 , 2 ], and it has been identified that hemodynamic factors play a significant role in the development and progression of such diseases [ 3 , 4 , 5 , 6 ]. For example, the development of atherosclerosis is based on the observation that vascular inflammation and plaques are distributed near side branches or arterials stenosis, where blood flow is non-uniform, and at the lesser curvature of bends where the blood flow rate is relatively low [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%